Adaptation and Validation of the Preparation for Future Care Needs Scale for Chinese Older Adults in Hong Kong. (24th June 2021) - Bai, Xue; Liu, Chang; Song, Yajun; Sörensen, Silvia
Abstract: Background and Objectives: Care planning can protect against or offset potential stressors in the caregiving stage and mitigate their detrimental effects. This study aimed to translate, adapt, and validate 2 short forms of the multidimensional, theory-guided scale measuring preparation for future care needs (PFCN) among Chinese older adults in Hong Kong. Research Design and Methods: Data were derived from a cross-sectional survey of 862 community-dwelling individuals aged 60 years and older. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted to assess the structural validity of the scales. Criterion-related validity, known-groups validity, and internal consistency were also examined. Results: EFA yielded a 14-item 4-factor (awareness, avoidance, decision making, and concrete planning) model, which was supported by CFA and explained 68.9% of the total variance. CFA also supported the structural validity of the 5-item scale. Criterion-related validity of the 2 scales was supported by their significant and positive correlations with domain-specific planning behaviors for retirement. Known-groups validity of the 2 scales was demonstrated by significant differences in scores between male and female older adults and scores between different educational levels and socioeconomic status. Cronbach's alphas for the internal consistency of the 14-item and 5-item scales were 0.889 and 0.774, respectively. Discussion and Implications: PFCN scales enable researchers and service practitioners to accurately understand and assess older adults' processes and efforts in care planning, facilitate the identification of individuals at risk from inadequate planning, and inform the development of interventions to enhance care preparation in target domains.